Aunt Dimity and the heart of gold - Atherton, Nancy (Aunt Dimity, 2019)
It's almost Christmas in the small English village of Finch--and everyone is sick. Though many of the villagers regretfully decline their invitations to Emma and Derek Harris's annual Christmas bash, Lori Shepherd has no intention of missing it. When the winter weather takes a turn for the worse, it's agreed that none of the guests will leave until morning. There's general merriment as the Christmas party becomes a pajama party--until a car appears in the winding driveway and promptly slides off the slick pavement and into a tree. Matilda "Tilly" Trout--a lost and scatterbrained, middle-aged woman--is mercifully unhurt and invited to stay the night. The next morning, Emma asks her guests if they would like a tour of the Manor--including a secret room she recently discovered. Several guests put forth guesses as to its purpose, but it's Tilly who correctly identifies the room as a chapel. Placing a palm on one of the ornately-carved panels, Tilly finds a hidden compartment concealing a pile of glittering treasure--including an exquisitely decorated heart made of solid gold. Where did it come from, and why does it look so different from everything else in the chapel? Why didn't Emma even know about this hidden compartment in her own home until now--and how did Tilly? With Aunt Dimity's otherworldly help, Tilly's bewildering store of knowledge, and the village's collective memory to guide her, Lori sets out to unravel the mystery behind the heart of gold. Lori and Tilly both discover they'll never spend another holiday alone--and Christmas finally comes to Finch!